Clinical Classification, Pregnancy Outcomes and Risk Factors Analysis of Severe Preeclampsia Complicated With HELLP Syndrome - Huang, Hui; Liu, Bo; Gao, Xia; Wang, Yunju (Frontiers in Surgery, 2022)
Purpose: To investigate the clinical classification, pregnancy outcomes and risk factors of pregnant women with severe preeclampsia (SPE) complicated with HELLP (hemolysis, elevated liver enzymes, and low platelets) syndrome. Methods: The clinical data of 50 pregnant women diagnosed with SPE complicated with HELLP syndrome in our hospital from January 2014 to January 2021 were retrospectively analyzed, and they were selected as the observation group. In addition, 50 pregnant and lying-in women diagnosed with preeclampsia (PE) in our hospital during the same period were selected as the control group. The clinical classification and pregnancy outcomes of pregnant women in the observation group were recorded. The age and gestational age of onset of pregnancy were recorded and compared between the two groups. Univariate analysis and multivariate logistic regression model were used to analyze the risk factors for its occurrence. Results: Among the 50 pregnant women in the observation group, 10 were type I, 35 were type II, and 5 were type III. Partial 33 cases, complete 17 cases. Among the fetuses, 35 were premature, 13 had fetal growth restriction, and 2 died in the perinatal period. 48 cases of cesarean section, 2 cases of induced labor, no natural labor. Univariate analysis showed that age, gestational age at onset, gestational age at termination of pregnancy, HGB, LDH, ALT, AST, TBIL, PLT, PT, and FIB were all associated with the occurrence of SPE complicated with HELLP syndrome (P<0.05). Multivariate logistic analysis showed that gestational age at onset, gestational age at termination of pregnancy, HGB, LDH, ALT, AST, TBIL, PLT, and FIB were independent risk factors for SPE complicated with HELLP syndrome (P<0.05). Conclusion: SPE complicated with HELLP syndrome has significantly increased adverse pregnancy outcomes and increased maternal and fetal mortality. Gestational age at onset and gestational age at termination of pregnancy are independent risk factors for its occurrence. Fully understanding the high-risk factors of HELLP syndrome, taking preventive measures in time, and carrying out targeted nursing can effectively improve the prognosis of pregnant women and reduce the risk of HELLP syndrome.